A Lesion-Proof Brain? Multidimensional Sensorimotor, Cognitive, and Socio-Affective Preservation Despite Extensive Damage in a Stroke Patient - García, Adolfo M.; Sedeño, Lucas; Herrera Murcia, Eduar; Couto, Blas; Ibáñez, Agustín (Frontiers in Aging Neuroscience, 2017)
In this study, we report an unusual case of mutidimensional sensorimotor, cognitive, and socio-affective preservation in an adult with extensive, acquired bilateral brain damage. At age 43, patient CG sustained a cerebral hemorrhage and, a few months later, she suffered a second (ischemic) stroke. As a result, she exhibited extensive damage of the right hemisphere (including frontal, temporal, parietal, and occipital regions), left Sylvian and striatal areas, bilateral portions of the insula and the amygdala, and the splenium. However, against all probability, she was unimpaired across a host of cognitive domains, including executive functions, attention, memory, language, somatosensory perception (e.g., taste recognition and intensity discrimination), emotional processing (e.g., experiencing of positive and negative emotions), and social cognition skills (prosody recognition, theory of mind, facial emotion recognition, and emotional evaluation). Her functional integrity was further confirmed through clinical interviews and contextualized observation of her performance in real-life tasks. In sum, CG’s case resists straightforward classifications, as the extent and distribution of her lesions would typically produce pervasive, multidimensional deficits. We discuss the rarity of this patient against the backdrop of other reports of atypical cognitive preservation, expound the limitations of several potential accounts, and highlight the challenges that the case poses for current theories of brain organization and resilience.